2017
DOI: 10.1073/pnas.1711184114
|View full text |Cite
|
Sign up to set email alerts
|

Molecular photoswitches mediating the strain-driven disassembly of supramolecular tubules

Abstract: Chemists have created molecular machines and switches with specific mechanical responses that were typically demonstrated in solution, where mechanically relevant motion is dissipated in the Brownian storm. The next challenge consists of designing specific mechanisms through which the action of individual molecules is transmitted to a supramolecular architecture, with a sense of directionality. Cellular microtubules are capable of meeting such a challenge. While their capacity to generate pushing forces by rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 43 publications
1
105
0
Order By: Relevance
“…The absence of any significant hypsochromic shifts demonstrates that the L 1 :TFA pairs remain stable upon UV irradiation without disassembly into the free ligand L 1 . However, the fact that marked hyperchromic UV/Vis absorption changes are observed upon UV irradiation (Figure a) are in accordance with a possible strain‐driven disassembly . Further keeping the solution at 298 K for 3 hours in the dark showed a decrease in absorbance without negligible shifts, indicating a reconstruction of the aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of any significant hypsochromic shifts demonstrates that the L 1 :TFA pairs remain stable upon UV irradiation without disassembly into the free ligand L 1 . However, the fact that marked hyperchromic UV/Vis absorption changes are observed upon UV irradiation (Figure a) are in accordance with a possible strain‐driven disassembly . Further keeping the solution at 298 K for 3 hours in the dark showed a decrease in absorbance without negligible shifts, indicating a reconstruction of the aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Storing energy in the form of strain build-up is difficult to achieve because in an equilibrium state, a locally high concentration of the disrupting cis form would be exchanged by trans building block from the solvent. By operating in water, a medium in which the cis building blocks are very poorly soluble, Fredy et al (2) were able to prevent such exchange, allowing the system to operate out of equilibrium. Notably, this process reflects the natural disassembly of cytoskeletal microtubules because irradiation does not immediately affect microtubule length while strain is accumulating, as was supported by simulations.…”
Section: O M M E N T a R Ymentioning
confidence: 99%
“…force is currently not converted into work, cytoskeletal microtubule disassembly has previously been employed to move cargo (16); a similar application for the system designed by Fredy et al (2) can easily be envisioned. Furthermore, the out-of-equilibrium state of these assemblies might be utilized in the development of synthetic systems with life-like properties.…”
Section: O M M E N T a R Ymentioning
confidence: 99%
See 1 more Smart Citation
“…v) A combination of UV light and agood (polar) solvent causes ring opening and subsequent reorganization into SP ext . utilizing the intrinsic curvature to prepare helically folded long supramolecular polymers (SP helical )b yi ntroducing an azobenzene photoresponsive chromophore [24][25][26][27][28][29] as an additional p-surface (compound 2,F igure 1a,bi). [22] We further demonstrated that the SP helical structure could be unfolded into an extended linear topology (SP ext )upon irradiation with UV light (Figure 1bii).…”
mentioning
confidence: 99%